The Politics of Reporting Reportable Diseases: A Methodological Review of the State-Researcher Clash (Tanzania Journal for Population studies and Development, 2018)
In December 2016, the media in Tanzania was preoccupied with questions on the presence of the Zika virus in Tanzania. The debate was sparked by a report of the National Institute of Medical Research (NIMR), which pointed out that traces of theZika virus had been identified in Tanzania. Within a short time, the government refuted the report and asked NIMR to retract the findings, arguing that the reporting process did not follow established procedures. Two central questions demand a closereview: first, why did the government demand that the report be retracted? Second, what are the procedures that should have been followed? In this methodological review of the reporting of reportable diseases, this paper attempts to examine theraison d’être for the tag of war between the two sides, and highlights the right procedures that should have been followed in the announcement of such findings. The review concludes with a methodological note to researchers and the reporting of findings in health-related studies.